2021
DOI: 10.1080/0734578x.2021.1958445
|View full text |Cite
|
Sign up to set email alerts
|

Multi-method geoarchaeological analyses demonstrates exceptionally rapid construction of Ridge West 3 at Poverty Point

Abstract: This report presents results of re-excavation and reanalysis of unit 5276N 4790E, located on Ridge West 3 (RW3) at the Poverty Point site. Jon Gibson excavated this unit and others in 1991 and argued that RW3 was constructed rapidly. We test the fast construction hypothesis by applying new methods (micromorphology, magnetic susceptibility, sequential loss-on-ignition) and by obtaining new radiocarbon dates. Before construction, the ground surface beneath RW3 was cleared and occupied. Preconstruction deposits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 14 publications
(6 reference statements)
1
23
0
Order By: Relevance
“…The association between posts and earthworks is a potentially more significant point of architectural variation between the two sites. The large posts erected during or after the construction of Mounds A and X are similar to those observed in the plaza of Poverty Point, but there is no evidence of posts being placed in earthworks at a similar scale at Poverty Point (Hargrave et al 2021; Kidder et al 2021; Ortmann and Kidder 2013). This suggests shared (although not identical) architectural practices in terms of form and ultimate function.…”
Section: Defining Poverty Point: the View From Jaketownmentioning
confidence: 80%
See 1 more Smart Citation
“…The association between posts and earthworks is a potentially more significant point of architectural variation between the two sites. The large posts erected during or after the construction of Mounds A and X are similar to those observed in the plaza of Poverty Point, but there is no evidence of posts being placed in earthworks at a similar scale at Poverty Point (Hargrave et al 2021; Kidder et al 2021; Ortmann and Kidder 2013). This suggests shared (although not identical) architectural practices in terms of form and ultimate function.…”
Section: Defining Poverty Point: the View From Jaketownmentioning
confidence: 80%
“…Although we do not know the full extent or form of the earthworks at Jaketown, geoarchaeological data discussed above demonstrate that both Mounds A and X were constructed rapidly, comparable to the construction of Mound A and the ridges at Poverty Point (Kidder et al 2021; Ortmann and Kidder 2013). This suggests similar methods of construction at the two sites, at least in terms of the pace of labor.…”
Section: Defining Poverty Point: the View From Jaketownmentioning
confidence: 92%
“…Floors are also suggested in Gibson's (1994:176, 2019) test of the Dunbar Mound, which is associated with a distinctively ritual space. Potentially extensive habitation evidence on or below the ridges (which may have involved structures) was removed by rapid ridge construction or destroyed by erosion/historic cultivation; the anthropogenic materials throughout the ridge fill reflect the churned-up use of midden-rich soils in their construction, not the incremental use of ridge surfaces when they were raised in elevation (e.g., Gibson 2001:105; Kidder et al 2021:224–225; Spivey et al 2015:150–151). In addition, geophysical survey has suggested that ridge construction was extremely complex, involving smaller “components” that were built and possibly modified, with both activities obliterating earlier or contemporary structural evidence (Hargrave et al 2021:203–205).…”
Section: Timber Circles At Poverty Pointmentioning
confidence: 99%
“…Poverty Point (16WC5) in West Carroll Parish, Louisiana, is a singular monumental Late Archaic site dating between about 1600 and 1000 BC: it comprises at least five mounds and six unique concentric ridges surrounding an open area (Figure 1). Recently placed on the World Heritage List of archaeological sites (US Department of Interior [USDOI] 2013), its earthworks and their implications have dominated discussion (Anderson 2004; Clark 2004; Ford and Webb 1956; Gibson 2004; 2019; 2021; Gibson and Carr 2004; Kidder 2011; Kidder et al 2021; Sassaman and Heckenberger 2004; Spivey et al 2015; Webb 1968). Likewise, despite extensive but largely small-scale excavations (USDOI 2013:81–83), the historiography of the site—quite simply a narrative of what went on there as we construct it—used to interpret the individual and collective importance of its parts remains problematic, although significant interpretations have been suggested (e.g., Gibson 2001, 2004, 2019, 2021; Kidder 2011; Kidder and Sassaman 2009; Spivey et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation